From being privileged to being localized?: Taiwanese businessmen in China - Lee, Chun-yi (Routledge, 2013)
Taiwanese businesses have invested in China for almost three decades. Political questions have always been the most sensitive issue for Taiwanese businesspeople (Taishang) in China. The most popular saying among them is, ‘Businesspeople only talk about business.’ Nevertheless, due to the changing cross-Strait relationship, Taiwanese businesspeople in China, more or less, unavoidably involve themselves in political issues. More precisely, they have indirect influence on Taiwan’s mainland policies and engage in China’s local politics. This chapter aims to analyse the Taishang’s political attitudes and political expectations cross the Strait. Interview data of Taishang in Tianjin, Kunshan and Dongguan was collected during 2004-2005 and 2009 field trips to China. The preliminary analysis revealed two points. Firstly, most Taishang do not have strong political identities. However, they do not just talk about businesses only. Taishang are keen to support those political parties which could be beneficial to their investment in China. Secondly, the idea of being Taiwanese in China has gradually faded in most Taishang’s minds. After living in China for more than two decades, most Taishang have already identified themselves as a Chinese person born in Taiwan. They also identify more with Chinese society rather than Taiwanese society.